Perancangan Sistem Informasi Rekapitulasi Daftar Rekening Ditagih (DRD) Pada Perumda TirtaUli Kota Pematang Siantar - , (Seminar Nasional Informatika (SENATIKA); 2023: Prosiding Seminar Nasional Informatika (SENATIKA) - IV, 2024)
Perumda TirtaUli Pematang Siantar City is one of the Regional Public Drinking Water Companies as a provider of clean water services for the community who are customers. and the only clean water supply company that is able to provide services for basic needs, especially clean water. So that customers feel satisfied with this service, plus complete, comfortable and quality facilities for customers are supporting factors for a service so that there are no more delays. water payments by customers, this can trigger arrears in paying water bills. Overall, search is a process of collecting obligations from customers from transactions that have occurred previously in accordance with existing documents. processing bills to customers is still experiencing difficulties because it still uses a manual recording system using sheets of paper, and bill processing often involves errors in data input which causes the data to be inefficient and precise. The goal is to design and create a water billing application using quirkical. By using PHP myadmin and MySQL database. The database created in the design of the billed account list is the DRD recapitulation, and there are 5 tables in the database, namely the login table, the DRD_list table, the customer table, the water_account table, and the region table.